A new species of Probreviceps (Amphibia: Anura) from the Eastern Arc Mountains, Tanzania - Loader, Simon P.; Channing, Alan; Menegon, Michele; Davenport, Tim R.b. (Zootaxa, 2006)
A new species of Probreviceps is described from the Ukaguru Mountains in Tanzania, and is distinguished morphologically by its pointed and ridged snout. The species also differs from other members of the genus in its call and mitochondrial DNA. An updated phylogeny of all known Tanzanian Probreviceps species and subspecies is presented, based on 12S and 16S rRNA mitochondrial sequences. An updated key of the species of Probreviceps is also given.